First measurement of the ratio of central-electron to forward-electron W partial cross sections in pp̄ collisions at s=1.96TeV - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; Aoki, M; et al. (2007)
We present a measurement of σ(pp̄→W)×B(W→eν) at s=1.96TeV, using electrons identified in the forward region (1.2<|η|<2.8) of the CDF II detector, in 223pb-1 of data. We measure σ×B=2796±13(stat)-90+95(syst)±162(lum)pb. Combining this result with a previous CDF measurement obtained using electrons in the central region (|η| 1), we present the first measurement of the ratio of central-electron to forward-electron W partial cross sections Rexp=0.925±0.006(stat)±0.032(syst), consistent with theoretical predictions using Coordinated Theoretical-Experimental Project on QCD (CTEQ) and Martin-Roberts-Stirling-Thorne (MRST) parton distribution functions. © 2007 The American Physical Society.